ESTABLISH THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND TELECOM GROWTH - Kumar, Pramit; Sharma, Ravindar Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Although India's cities and metro areas are densely populated, they only account for 30% of the nation's total population. Data from 2012 indicates that India's overall tele-density reached 76.66%. Urban areas boasted a tele-density of 167.46%, while rural regions lagged behind at 32.52%. Trends in both developed and emerging countries reveal that younger generations are more frequent internet users compared to older ones. In emerging economies, 30% of individuals under 25 use the internet, compared to 23% of those aged 25 and above. There also lies a significant opportunity for developing nations to connect schools and increase enrollment rates, considering that 70% of the under-25 population amounting to 1.9 billion people have yet to transition to internet usage. Evaluations concerning whether mergers lower prices, influence competition, improve opportunities in rural areas, as well as long-term versus immediate development, have been examined. The results indicated that service providers shared similar perceptions about the telecom sector's impact on rural areas.